A new supramolecular isomer of p-aminobenzoate Zn(II) coordination polymer: Structure and photoluminescent property. (1st October 2019) - Crisan, Manuela E.; Gorobet, Anastasia; Siminel, Anatolii V.; Bourosh, Paulina N.; Croitor, Lilia
Graphical abstract: A new coordination polymer {[Zn( p ABA)2 (H2 O)]·H2 O} n (1 – P 2/ c ) was prepared and characterized by FT-IR spectroscopy, TGA, and single-crystal X-ray diffraction method. The crystallographic investigation attests that1 and two known complexes IWORET ( P 21 / c ) and YIWDEO ( P 21 ) are supramolecular isomers. The new solid reveals blue-violet and green photoluminescence upon excitation with ultraviolet light. Abstract: A new supramolecular isomer of hydrated Zn(II) coordination polymer {[Zn( p ABA)2 (H2 O)]·H2 O} n (1 ) was prepared by a combination of multifunctional p -aminobenzoic acid ( p ABAH) with hydrated zinc tetrafluoroborate and then structurally compared with two previously known isomers IWORET and YIWDEO (refcodes in the Cambridge Structural Database). The new compound was characterized by FT-IR spectroscopy, thermogravimetric analysis, and single-crystal X-ray diffraction method. The crystallographic investigation shows that p ABA anions bind the metal atoms in1 and IWORET through the amine nitrogen and the carbonyl oxygen in a double-stranded bridge fashion giving rise a 1D coordination chain (1 ) and 2D layer (IWORET). In YIWDEO isomer, p ABA − presents two different coordination modes (monodentate and bridging bidentate) extending the structure to 1D coordination polymer. The new solid reveals blue-violet and green photoluminescence, while IWORET crystals show violet emission upon excitation with ultraviolet light.